List of Trade Unionists & Labour Party Members [International Brigade]
1937 034-0192-012 10. *M. Goldberg Mile End Labour Party ord. member. Dependant: D. Hooper A.E.U. London, Kilburn Dependant: Mrs. Hooper, 30 St. Julian Rd., Kilburn N.W. (£1-15-0) A. Hurd NUS Liverpool Dependant: Mrs. R. Hurd, 26 Nelson St., Liverpool 1. (£2-5-0) D. McEwan Dyers & Bleachers Alexandria. Dependant: Mrs. D. McEwan, c/o Doyle, 7 Leven Vale, Alexandria. (£1-5-0). J. McGill BWUAFL, 36 London Ont. Dependant: A. McDade TGWU 7/18 Dependant: Mrs. McDade, 112 Ellesmere St., Glasgow N. (£1-10-0) J. Murray AEU Milton Branch President Dependant: F. Robertson NUF Greens Home Dependant: W. Tattam TGWU St. Heller Carshalton. Dependant: Mrs. Tattam, 169 Gander Green Lane, Sutton, Surrey. (£1-10-0). OTHER ORGANISATIONS C. Conway IGTWU Dublin No.5 Shop Steward Dependant: F .Goldency Workers Union of Ireland Skinhige Br. Dependant: K. McPhee Fed. Seamens Union Australia, Sidney Br. Dependant: F. Neary American Students Union Dependant: J. Palzard NUWa Canada. Dependant: F. Ryan NUJ Dublin Dependant: H. Spiller New Zealand Waterside Workers Union Napier Br.Wellington Dependant: 292/946/34/193(x)